If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (b + 11)(b + -11) = 0 Reorder the terms: (11 + b)(b + -11) = 0 Reorder the terms: (11 + b)(-11 + b) = 0 Multiply (11 + b) * (-11 + b) (11(-11 + b) + b(-11 + b)) = 0 ((-11 * 11 + b * 11) + b(-11 + b)) = 0 ((-121 + 11b) + b(-11 + b)) = 0 (-121 + 11b + (-11 * b + b * b)) = 0 (-121 + 11b + (-11b + b2)) = 0 Combine like terms: 11b + -11b = 0 (-121 + 0 + b2) = 0 (-121 + b2) = 0 Solving -121 + b2 = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '121' to each side of the equation. -121 + 121 + b2 = 0 + 121 Combine like terms: -121 + 121 = 0 0 + b2 = 0 + 121 b2 = 0 + 121 Combine like terms: 0 + 121 = 121 b2 = 121 Simplifying b2 = 121 Take the square root of each side: b = {-11, 11}
| 4y+6=54 | | 5x^2+4xy-y^2=0 | | x^2-30x+1=0 | | 2x-3y=44 | | 3x^2+2x=4-7x | | x^2+4mx+8-4m=0 | | (12x^2)= | | 4m^2=24 | | y^(1/4) | | x^2-300x-30000=0 | | -1/3(3w-15)=-1/5(25-5w) | | 20p/3=40*3 | | (2y+1)(y-3)-3y(y+2)=y(2-y)+10 | | 2n-1=5n | | 8x12/4-?=2 | | 5m+12y=7y | | 4(2x+1)=6(x+12) | | 9(2x+3)=3(5x+4) | | 5(x+1)=4x+17 | | 3(x+9)=x+13 | | 4(x+4)=3x+22 | | x^2-90x-450=0 | | 5m+12=8md | | 2x+1=x^2-2x+1 | | 2682/8 | | ax^4+bc+c=0 | | 5-n/3=1 | | 8*3m=-3+6m | | x*0.07=1760 | | -2x-(x-1)+8=0 | | 4m+3m=1880 | | 48x+7y=1 |